2000
DOI: 10.1143/jjap.39.l633
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Optical Recording on a Polyester Film Having Photochromic Thioindigo Moieties in the Main Chain

Abstract: A multi-layer node is described for multi-functional sensor networks. The generation-4 smart sensor node (G4SSN) is light weight, has a small footprint, and is low power to support dedicated, embedded applications. It has core layers for data sensing, data processing and wireless networking. The modular physical layout is built around a flexible, multi-channel bus architecture and routing protocols are easily tailored. Additional stackable layers and devices can be easily configured and programmed to meet spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Photochromism has attracted much attention because of their potential applicability to photonic devices, such as optical memories and photooptical switches. Among a number of photochromic compounds, diarylethene derivatives are the most promising compounds for these applications because of high durability for coloring/decoloring cycles, thermal stability of both isomers, and rapid response. Single-crystalline photochromism is also a unique character of diarylethene derivatives. We have reported some 1,2-bis(3-thienyl)perfluorocyclopentene derivatives that undergo single-crystalline photochromism. , Both photocyclization and photocycloreversion processes of 1,2-bis(2,5-dimethyl-3-thienyl)perfluorocyclopentene crystals have been elucidated in situ by X-ray crystallographic analysis. , …”
Section: Introductionmentioning
confidence: 99%
“…Photochromism has attracted much attention because of their potential applicability to photonic devices, such as optical memories and photooptical switches. Among a number of photochromic compounds, diarylethene derivatives are the most promising compounds for these applications because of high durability for coloring/decoloring cycles, thermal stability of both isomers, and rapid response. Single-crystalline photochromism is also a unique character of diarylethene derivatives. We have reported some 1,2-bis(3-thienyl)perfluorocyclopentene derivatives that undergo single-crystalline photochromism. , Both photocyclization and photocycloreversion processes of 1,2-bis(2,5-dimethyl-3-thienyl)perfluorocyclopentene crystals have been elucidated in situ by X-ray crystallographic analysis. , …”
Section: Introductionmentioning
confidence: 99%
“…To avoid using a regenerative amplifier, one approach is to adopt polymer material as the recording medium because of their low threshold energy for recording. [7][8][9][10][11] For example, Yamasaki et al have reported recording on poly(methyl methacrylate) (PMMA) by microexplosion. 10) In this write-once read-many (WORM) recording, the threshold energy for recording is 5 to 7 nJ/pulse.…”
mentioning
confidence: 99%
“…In recent years, various systems and recording media for a three-dimensional (3D) optical memory have been demonstrated aiming at realization of a terabyte optical memory system. [1][2][3][4][5][6][7][8][9][10][11] In most of these reports, which assume multiphoton absorption (MPA) using femtosecond pulses, a regenerative amplifier is used together with a femtosecond oscillator in order to realize the recording irradiance of several TW/cm 2 at the focal position. To avoid using a regenerative amplifier, one approach is to adopt polymer material as the recording medium because of their low threshold energy for recording.…”
mentioning
confidence: 99%
“…A 3D system based on multiphoton absorption (MPA) using a femtosecond laser is an attractive candidate, and there are a number of reports on 3D recording principles and recording media. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] We have proposed a write-once read-many (WORM) recording medium which consists of poly(methyl methacrylate) (PMMA), a photoacid generator (PAG), and a pH-sensitive organic dye. 14) This recording medium has two advantages.…”
Section: Introductionmentioning
confidence: 99%